Husband-wife discrepancies in fertility-related attitudes and perceptions levels, correlates and their influence on contraceptive practice - Asis, Maruja Milagros B. 1958- (1984)
Based on husband-wife data from the 1970 Community Outreach Survey, the study aimed to: identify significant husband-wife discrepancies in fertility-related attitudes and perceptions; determine the demographic, socioeconomic and communication correlates of husband-wife discrepancies; determine the influence of husband-wife discrepancies on couples’ contraceptive practice; and examine whether the levels of husband-wife discrepancies are associated with the type of contraceptive methods adopted by users.
The study hypothesized that attitudinal discrepancies between couples may be brought about by demographic, socioeconomic and communication factors. The greater the differences in couples’ characteristics, the more likely one to exhibit discrepancies in fertility-related attitudes and perceptions. Consequently, these discrepancies influence couples’ contraceptive practice: the lower the level of husband-wife discrepancy, the more likely are couples to practice contraception. As regards the contraceptive choice of couples, it was advanced that couples with low levels of discrepancy would tend to use “joint methods” (e.g. withdrawal, rhythm) since use of such methods rests on the cooperation of both spouses. On the other hand, couples with high levels of discrepancy would tend to use “single methods” (e.g. pills, IUD, sterilization) in as much as their use rests with either spouse and thus demand less cooperation from both spouses.
Levels of husband-wife discrepancy in selected attitude and perception variables were obtained from proportions of discrepant responses. Where discrepant responses amount to at least 20 per cent of the total responses, further analysis – i.e. determining the correlates of husband-wife discrepancies and consequently relating these discrepancies with couples’ contraceptive behavior – was done. Relationships were analyzed in a bivariate context. Chi-square and gamma were employed to test the relationship between variables, and where appropriate, gamma was likewise used to indicate the strength and direction of relationships.
The study found out that the proportion of discrepant couples could range from 15 to 44 per cent on selected attitude and perception variables. These discrepancies were skewed (i.e. to lean towards the attitude of either spouses) to either the husbands’ or the wives’ attitude. In certain cases, no skewness was evident indicating that the proportion of discrepant responses is equally distributed in the two discrepant categories.
The study did not find much support for the hypothesized relationship between heterogeneity in couples’ characteristics and husband-wife discrepancies. Instead, it was either the husbands’ or the wives’ characteristics taken singly or the shared characteristics of couples (specifically duration of marriage and parity) which proved to be significantly associated with levels of husband-wife discrepancy. For most of the attitude and perception variables, levels of husband-wife discrepancy were negatively associated with age, duration of marriage, parity and exposure to family planning information from interpersonal sources, program personnel and the mass media.
As to the relationship between husband-wife discrepancies and contraceptive behavior, the study demonstrated that low levels of husband-wife discrepancy in attitudes supportive of family planning (defined here as positive consistency) were generally associated with higher levels of contraceptive practice. Thus, couples who similarly reported that they wanted no more children, that they approved of modern contraception, and who perceived that their reference groups approved of modern contraception were more likely to use contraception than discrepant couples. Between husband and wives, the latter’s attitude appeared to be more closely associated with contraceptive practice. Regardless of the wives’ stand, use tended to be high when husbands wanted no more children and when husbands wanted no more children and when they approved of modern contraception. Contrary to the advanced relevant hypotheses, the study observed that consistent couples tended to be users of single methods while discrepant couples were more likely to be users of joint methods. It is probable that these tendencies are more reflective of couples’ openness towards modern contraception than the hypothesized influence of husband-wife interaction and contraceptive choice. The importance of consistency in husband-wife attitude to contraceptive behavior is reinforced by the study’s findings on continuation of use of methods. It was discovered that couples who were both satisfied with the use of a particular method were most likely to continue the use of such a method, discrepant couples were less likely to; and couples who both stated that they were not satisfies altogether stopped or shifted to other methods.
Vita.
Thesis
Keywords: Fertility, Human -- Philippines; Birth control -- Philippines; Contraceptives; Husband and wife -- Attitudes. -- Philippines